Penerapan Pembelajaran Calistung Pada Anak-Anak di Desa Simanungkalit - Desmawati Gulo; Debora Sinaga; Helena Munthe (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Calistung learning is part of the Early Childhood Education (PAUD) Curriculum. Basically, Khalistan learning focuses on teaching reading, writing and arithmetic skills. This is stated in Appendix I to the Regulation of the Minister of Education and Culture of the Republic of Indonesia (Permen) No. 137, Content Standards for Developmental Achievement Levels for Children 4-5 Years and 5-6 Years (STPPA). 2014. This introduction aims to prepare children to continue to the next level of education, namely basic education. However, the ideal Calistung PAUD learning model is still a serious problem in a broader context, especially when combined with the possibility of further SD/MI entrance exams in the form of the Calistung test. Many elementary schools/MIs hold Calistung entrance exams as a prerequisite for accepting new students according to standards